PENGARUH STRATEGI PROMOSI INDIHOME TERHADAP MINAT KONSUMEN DI KOTA BIMA - Muhammad Aras Nuryakin; Herry Nurdin (Universitas Sarjanawiyata Tamansiswa, 2021)
The rapid development of network access technology and internet-based technology makes it possible for service operators to be able to provide various services, one of which is fiber optic network services. This study aims to determine and analyze the effect of Indihome's promotional strategy on consumer interest in Bima City. This type of research is associative by using quantitative data from primary data sources. The research instrument is a Likert scale questionnaire. The population used in this study is all Indihome WIFI users in Bima City, the number of which is not known with certainty. The sample in this study was 96 respondents using the Bernoulli formula. The sampling technique in this study is purposive sampling, which is a sampling technique with certain considerations, what the authors consider from the sample to be studied are the people of Bima City who already know about the existence of Indihome products offered by PT. Telekomunikasi Indonesia, Tbk. The results showed that the Indihome promotion strategy had an effect on consumer interest in the City of Bima with a strong relationship level and the effect was 37.8%.